Impact of COVID-19 on Cardiothoracic Surgery: Experience of Alexandria (Egypt) Main University Hospital - Hemead,Hanan M. (2022)
ABSTRACT Introduction: The current coronavirus pandemic has greatly strained the limited resources that had previously maintained the sustainability of the high-cost cardiothoracic surgeries in low-income countries like Egypt. Methods: Hospital databases and patients’ records were reviewed to evaluate the impact of the pandemic on the workflow and waiting lists. Postoperative patients were contacted by telephone for follow-up, as well as preoperative patients whose operations were cancelled. Regular virtual meetings were held, and residents were asked to discuss the stresses, challenges, and their suggestions for the gradual resumption of services. Residents’ logbooks were evaluated to assess the disruption of the surgical exposure compared to 2019. Results: While thoracic surgeries have continued to thrive, cardiac surgeries have witnessed the worst consequences, including cancellation of all surgeries, expansion of waiting lists, patients’ non-compliance with follow-up, and impaired surgical exposure of junior residents. Conclusion: The gradual recovery of cardiac surgery services in Alexandria (Egypt) is being carefully planned, taking into consideration the backlog of cases and the shortage of screening kits. Careful tiering and triaging of patients by a multidisciplinary team, as well as seeking alternative assessment tools for trainees, are the main lines of our action plan.